Nowe oblicza Europy. Reformy prawne i polityczne w Unii Europejskiej (cykl seminriów w 2003 r.): [New faces of Europe. Legal and political reforms in the European Union (seminar series in 2003)] (Studia Prawnicze / The Legal Studies, 2003)
Sprawozdanie z cyklu semianriów INP PAN pn.  Nowe oblicza Europy. Reformy prawne i polityczne w Unii Europejskiej, zorganizowanych w 2003 r. Report from the ILS PAS seminar series entitled New faces of Europe. Legal and Political Reforms in the European Union, organized in 2003